Implementasi Pembelajaran Tematik Terpadu Menggunakan Pendekatan Saintifik di Kelas II Sekolah Dasar (Studi Literatur) - Rahmadona, Three; Astimar, Nelly (Universitas Negeri Padang, 2021)
The success in implementing integrated thematic learning using a scientific approach, starts from the skills of an educator in preparing lesson plans. However, there are still educators who are not perfect in making lesson plans, so the authors are interested in making learning designs with a scientific approach. The method used is literature study, by comparing the various research results of the scientific approach. From the observations of the five scientific lesson plans that the author found, it is concluded; the suitability of RPP by M (2015) is 93.22% with a total value of 55 out of 59 total scores; K (2015) amounted to 88.1% with a total value of 52 out of 59 total scores; H (2020) of 83.05% with a total score of 49 out of 59 total scores; B (2016) of 84.75% with a total value of 50 out of 59 total scores; and R (2018) amounting to 84.75% with a total value of 50 out of 59 total scores. From the results of the lesson plans that the author made, the suitability of the lesson plans was 100% with a total value of 59 of the 59 total scores.